MANAJEMEN SALON YANG EFEKTIF UNTUK MENINGKATKAN KEPUASAN PELANGGAN DI ADYAN SALON - Nabila Azzahra; Maysya Majesty Tara Bahan; Ruth Vinita Br Siahaan; Aulia Nur Hermawan; Sri Endah Wahyuningsih (STKIP Subang, 2026)
This article aims to explain the implementation of efficient salon management to enhance customer satisfaction at Adyan Salon by analyzing the POAC management functions (Planning, Organizing, Executing, Controlling), the 5W1H technique, and the 6M management aspects. This study employs a qualitative methodology, combining direct observation and in-depth interviews with the salon owner to investigate business planning, task allocation, the customer service framework, human resource management, and operational assessment. The data obtained is then evaluated descriptively to illustrate the application of salon management in daily operations. The research findings reveal that the proprietor of Adyan Salon intends to operate the business not solely for profit but also to generate employment opportunities and function as an educational platform for individuals aspiring to progress in the beauty industry, while adjusting services to align with emerging beauty trends and technologies. From an organizational standpoint, despite the family-oriented and informal structure, the distribution of responsibilities according to expertise operates efficiently, hence facilitating seamless operations. The implementation of customer service procedures is organized from client welcome, guaranteeing comfort, delivering services based on needs, to facilitating possibilities for complaints or changes of outcomes. Oversight is conducted by senior personnel and augmented through monthly assessments that focus on customer grievances, service challenges, product availability, and quality enhancement efforts. The systematic and continuous evaluation of management at Adyan Salon enhances service quality, hence facilitating customer happiness.